2021
DOI: 10.1002/slct.202100507
|View full text |Cite
|
Sign up to set email alerts
|

The Formation and Conducting Mechanism of Imidazole‐Gold Molecular Junctions

Abstract: The formation mechanism and electronic transport properties of imidazole sandwiched between gold electrodes are investigated using the non‐equilibrium Green's function formalism combined with density functional theory. Our calculations show that the imidazole radical bridges the gold electrodes and the covalent Au−N bonds formed at the molecule‐electrode interfaces enhance the junction stability. In contrast, adding one more electron to the junction, which corresponds to the imidazole radical anion, will incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 41 publications
5
14
0
Order By: Relevance
“…19−22 Recently, we have reported that the Au−N bond is a donor−acceptor one when an imidazole molecule binds to the gold electrode via the pyridine-like nitrogen atom. 23 In this case, the density of states (DOS) projected onto the imidazole molecule indicates that the LUMO is much closer to E F than the HOMO. Interestingly, once the hydrogen atom bonded to the pyrrole-like nitrogen is removed, the Au−N bond becomes covalent, and now it is the HOMO that is closer to E F .…”
mentioning
confidence: 90%
See 4 more Smart Citations
“…19−22 Recently, we have reported that the Au−N bond is a donor−acceptor one when an imidazole molecule binds to the gold electrode via the pyridine-like nitrogen atom. 23 In this case, the density of states (DOS) projected onto the imidazole molecule indicates that the LUMO is much closer to E F than the HOMO. Interestingly, once the hydrogen atom bonded to the pyrrole-like nitrogen is removed, the Au−N bond becomes covalent, and now it is the HOMO that is closer to E F .…”
mentioning
confidence: 90%
“…The hydrogen atom bonded to the latter can be removed either in basic solutions or by exposing it to oxygen. , Apart from the extensive studies in biology and electrochemistry, imidazole is winning growing attention as an aurophilic anchoring group in single-molecule junctions. It has been experimentally confirmed that both the nitrogen atoms in the imidazole moieties address reliable binding sites to form stable single-molecule junctions with gold electrodes. Recently, we have reported that the Au–N bond is a donor–acceptor one when an imidazole molecule binds to the gold electrode via the pyridine-like nitrogen atom . In this case, the density of states (DOS) projected onto the imidazole molecule indicates that the LUMO is much closer to E F than the HOMO.…”
mentioning
confidence: 93%
See 3 more Smart Citations